2021
DOI: 10.1126/scisignal.abf1117
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic short linear motifs in ACE2 and integrin β 3 link SARS-CoV-2 host cell receptors to mediators of endocytosis and autophagy

Abstract: The spike protein of SARS-CoV-2 binds the angiotensin-converting enzyme 2 (ACE2) on the host cell surface and subsequently enters host cells through receptor-mediated endocytosis. Additional cell receptors may be directly or indirectly involved, including integrins. The cytoplasmic tails of ACE2 and integrins contain several predicted short linear motifs (SLiMs) that may facilitate internalization of the virus as well as its subsequent propagation through processes such as autophagy. Here, we measured the bind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 74 publications
5
74
1
Order By: Relevance
“…Similar PDZ interactions manifested by ACE2-NHERF1 have also been observed between ACE2 and NHERF3, a putative ACE2-interacting partner (Kliche et al, 2021). As shown in Figure S2, full-length myc-ACE2 overexpressed in HEK293 GnTI À cells coimmunoprecipitates with NHERF3-FLAG as observed for NHERF1.…”
Section: Ll Open Access Isciencesupporting
confidence: 73%
See 1 more Smart Citation
“…Similar PDZ interactions manifested by ACE2-NHERF1 have also been observed between ACE2 and NHERF3, a putative ACE2-interacting partner (Kliche et al, 2021). As shown in Figure S2, full-length myc-ACE2 overexpressed in HEK293 GnTI À cells coimmunoprecipitates with NHERF3-FLAG as observed for NHERF1.…”
Section: Ll Open Access Isciencesupporting
confidence: 73%
“…An early report showed that deletion of the ACE2 C-terminal tail causes significant change in SARS-CoV incorporation (Inoue et al, 2007), implying an important role for the carboxy-terminus region and its potential interaction with unidentified intracellular proteins mediating viral entry. While the present study was in progress, a report postulated that the interacting partners associated with the cytoplasmic tail of ACE2 are likely to be PDZ-containing (Singh et al, 2009) (PDZ is an acronym for the first three identified proteins sharing a highly similar structural domain: Postsynaptic density 95/Disc large/Zonula occludens-1) proteins SNX27, NHERF3, or SHANK based on bioinformatics analysis and fluorescence polarization assay using FITC-labeled C-terminal peptides of ACE2 and individual truncated PDZ domains from the three mentioned proteins (Kliche et al, 2021). Functional evidence for that proposition was not provided.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides mechanistic evidence for the functionality of extracellular ligand-binding domains of integrin b1 and cytoplasmic tails of integrins in general, 24,28 which offer possible molecular links between ACE2 and integrins. We show that Mn 2+ , which induces integrin extension and high affinity ligand binding, enhances the cell entry of SARS-CoV-2 R18 .…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that the concomitant elevation of these integrins and the upregulation of ACE2 in an organ may render it more susceptible to preferentially binds to and inhibits activated forms of α 5β1 in areas of inflammation, hypoxia and angiogenesis [30]. ATN-161 also binds to integrin α vβ3 [30], an additional integrin that has been implicated in SARS-CoV-2 pathogenesis [33,32], and is safe, well-tolerated in human clinical trials (cancer) with no dose limiting toxicity [28,66], and can be administered i.v., i.p., and intranasally [31,67]; The latter may support a more readily accessible means of COVID-19 treatment as well as afford a prophylactic approach which is currently under investigation in our laboratory.…”
Section: Atn-161 Effects On the Expression Of Virus In Sars-mentioning
confidence: 99%
“…We further demonstrated that the small pentapeptide α 5β1 integrin inhibitor ATN-161 could inhibit this binding and also decrease SARS-CoV-2 infection and cytopathy in cultured vero-E6 cells [26]. ATN-161 has several properties that make it potentially attractive as a novel SARS-CoV-2 therapy; it is safe and welltolerated with no dose-limiting toxicity in phase I cancer clinical trials [28], has demonstrated invivo efficacy in mice against a different beta coronavirus, porcine hemagglutinating encephalomyelitis virus (PHEV) [29] as well as other disease/injury models [30,31], and can also bind to and inhibit integrin α vβ3 which is similar to α 5β1 integrin that has also been implicated in SARS-CoV-2 infection [32,33]. In the present study we examined the therapeutic potential of ATN-161 in a human ACE2 receptor-expressing K18 mouse model of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%